Der Reformator Martin Luther 2017. Eine wissenschaftliche und gedenkpolitische Bestandsaufnahme - Schilling, Heinz (Schriften des Historischen Kollegs, 2015)
There is broad historical awareness for Martin Luther and the Protestant Reformation in Germany, Europe, and the ´West` as a whole, but given the persistent myths about the persona and work of this reformer, there is a need for a radical re-historicization of Luther and his reception. This compendium seeks to stimulate such a reevaluation in order to place the 500-year commemoration of the Protestant Reformation on sound historical footing.